Islamic Financial Literacy and its Determinants among University Students: An Exploratory Factor Analysis - Rahim, Siti Hafizah Abdul; Rashid, Rosemaliza Abdul; Hamed, Abu Bakar (International Journal of Economics and Financial Issues, 2016)
This study aims todevelop the constructs in order to test the validity and reliablity of Islamic financial literacy and its determinants such as hopelessness, religiosity and financial satisfaction. The development of validated constructs for Islamic financial literacy is crucial since most contemporary research focus on conventional financial literacy which contains some elements that are not compatible with the principles of Islamic finance. The data for the study was collected via structured questionnaires distributed to 200 students of Universiti Utara Malaysia. An exploratory factor analysis using SPSS programme were used to analyze the data. The results show that only 7 items load reliably in Islamic financial literacy construct. Specifically, religiosity was found to exhibit the highest variance followed by hopelessness and financial satisfaction. This paper enables future researchers to expand the knowledge in the area of Islamic financial literacy by providing validated constructs to assess Islamic financial literacy among university students. Keywords: Islamic financial literacy, exploratory factor analysis, validity JEL Classifications: I2, I3